Winter oilseed rape semi‐dwarf hybrids are not discriminated by front‐border effects in yield trials. Issue 4 (3rd June 2020) - Schierholt, Antje; Holzenkamp, Karin; Hartwig, Henning; Gertz, Andreas; Becker, Heiko
Abstract: For oilseed rape ( Brassica napus L.), hybrid varieties of two growth types, semi‐dwarf and normal, are on the market. So far, the acceptance of semi‐dwarf hybrids is very limited, though they have several advantages such as higher N efficiency and drought tolerance. It is undecided whether both growth types are influenced in the same way by front‐border effects in plot yield trials. This study analyzed if semi‐dwarf hybrids were discriminated against in yield trials, due to differences in the exploitation of the front‐border area, since they could not lean and grow as far into the adjacent path due to a reduced height compared to normal type hybrids. From 2016–2018, eight pairs of near‐isogenic hybrids, bzh semi‐dwarf and normal type hybrids, were grown in three environments, with three replications and two treatments: Plants were harvested with and without the plot front‐border, and seed and straw yields were determined. Root electrical capacitance was also measured. Semi‐dwarf hybrids outperformed normal type hybrids in seed yield in the dry season of 2018, whereas the reverse happened in the more humid season of 2017. Across environments, semi‐dwarf hybrids had a higher positive front‐border effect (11.2%) than normal type hybrids (9.6%), leading to a relative overestimation of semi‐dwarf hybrid yields. There was no significant difference in root electrical capacitance between growth types across environments. It could be concluded that semi‐dwarf hybrids were not disadvantaged with regard to front‐border effects in plot trials, when compared to normal type hybrids. However, elimination of the plot front‐border area might improve comparisons between semi‐dwarf and normal type cultivars.